The Devil's Playground - Goldin, Nan 1953- (Phaidon, 2003)
THE DEVIL'S PLAYGROUND is the most significant book published to date on Nan Goldin (b. 1953), one of the most prominent and influential contemporary photographers. It contains Goldin's latest works alongside earlier classics, including images from new series such as ELEMENTS, 57 DAYS, STILL ON EARTH, and FROM HERE TO MATERNITY, many of which are published here for the first time. This book is an intimate and compelling photographic portrait, telling personal stories of relationships and identity while chronicling different eras and the passage of time. Goldin's photographic sequences are interspersed with texts, poems, and lyrics by prominent writers.
Keywords: Goldin, Nan <1953->; Goldin, Nan -- 1953-; Foto's; Photographie artistique; Photographie de nus; Photographie érotique; Portraits (Photographie); Photography, Artistic; Porträtfotografie; Bildband